Clinical Outcome of Autologous Hematopoietic Stem Cell Transplantation in Stiff Person Syndrome: A Literature Review - Dedeh Supantini; Fellicia Meiliana Fransisca; Ardo Sanjaya; Julia Windi Gunadi; Sylvia Tanumihardja (Universitas Malahayati, 2026)
Stiff person syndrome (SPS) is a rare immune-mediated neurological disorder characterized by progressive muscle stiffness and painful spasms that significantly impair functional ability. Although symptomatic and immunomodulatory therapies are commonly used, some patients remain refractory to standard treatments. Autologous hematopoietic stem cell transplantation (aHSCT) has been proposed as a potential therapeutic option for severe or treatment-resistant cases. This literature review aims to evaluate the clinical outcomes and safety of aHSCT in patients with SPS. A narrative literature review was conducted using published studies reporting the use of aHSCT in SPS, including clinical trials, cohort, case series, and case reports. Relevant articles were identified through PubMed and Google Scholar, limited to studies published within the last ten years. A total of 134 articles were initially identified, followed by a selection process, and five eligible articles were included in this review. The reviewed studies demonstrated that aHSCT may lead to clinical improvement in selected patients with refractory SPS. Autologous HSCT reduced muscle stiffness and improved functional status. Treatment responses varied, and some non-responders were reported; however, overall clinical outcomes were favorable with acceptable safety profiles. In conclusion, aHSCT may be considered a potential therapeutic option for severe or treatment-resistant SPS, although further prospective studies are needed to confirm its efficacy and safety.